2023
DOI: 10.1097/pq9.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

New strategies to Reduce Unnecessary Antibiotic Use in the NICU: A Quality Improvement Initiative

Alfonso Pantoja,
Scott Sveum,
Sandra Frost
et al.

Abstract: Introduction: Early-onset sepsis (EOS) and late-onset Sepsis (LOS) are common diagnoses entertained in sick newborns treated in neonatal intensive care units (NICUs), and antibiotics are the medications most prescribed in NICUs. Antibiotic stewardship programs have an important impact on limiting unnecessary antibiotic use. Methods: Following the Model for Improvement, between 2/1/16 and 1/31/17, at a level 3 NICU, a multidisciplinary team implemented PDSA cycles to promote antibiotic stewardship practices f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…4 Antibiotics are the most common medication prescribed in NICUs, with wide variability in use, regardless of the level of care or complexity of patients. 5 On any given day, 40% of infants admitted to a NICU are prescribed antibiotics, with an estimated 90% exposed to antibiotics over the duration of their NICU stay. 3 A recent study published in The Lancet Regional Health-Southeast Asia found that the most commonly prescribed antibiotics in Southeast Asia are now only 50% effective at treating sepsis and meningitis in newborns.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…4 Antibiotics are the most common medication prescribed in NICUs, with wide variability in use, regardless of the level of care or complexity of patients. 5 On any given day, 40% of infants admitted to a NICU are prescribed antibiotics, with an estimated 90% exposed to antibiotics over the duration of their NICU stay. 3 A recent study published in The Lancet Regional Health-Southeast Asia found that the most commonly prescribed antibiotics in Southeast Asia are now only 50% effective at treating sepsis and meningitis in newborns.…”
mentioning
confidence: 99%
“…6 Furthermore, there is increasing evidence that preterm infant antibiotic exposure is associated adverse outcomes including alteration in the intestinal microbiome, necrotizing enterocolitis, invasive fungal infections, retinopathy, and late-onset sepsis. 5 Early life antibiotic exposure is also associated with future health problems including childhood obesity, asthma, allergic disorders, and inflammatory bowel disease. 5 Therefore, it is important to find strategies to reduce antibiotic use in the NICU patient population.…”
mentioning
confidence: 99%
See 3 more Smart Citations